A kind of ordered mesoporous aluminum silicon carbide and preparation method thereof
By using ordered mesoporous silica as template agent, the problems of carbon residue and channel blockage in aluminum silicon carbide materials are solved, and the regular channel structure and high thermal conductivity of aluminum silicon carbide are realized, ensuring the temperature resistance of the material and Aluminum element distribution uniformity.
Patent Information
- Application Number
- CN202411242339.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-05
AI Technical Summary
In the prior art, when preparing aluminum silicon carbide materials, there are problems such as carbon residue, blockage of channels, low thermal conductivity and uneven distribution of aluminum elements, which affect the material's temperature resistance and thermal conductivity.
Using ordered mesoporous silica as hard template agent, the aluminum silicon carbide precursor is fully filled in its pores, and the silica is dissolved by sodium hydroxide to obtain aluminum silicon carbide material with regular pore structure and high specific surface area. , the ratio of aluminum silicon carbide to silicon dioxide is controlled to be 1:0.5~2 to ensure the connectivity and thermal conductivity of the pore structure.
The thermal conductivity of aluminum silicon carbide materials has been improved, the channel structure is regular and connected, the thermal conductivity reaches 201-208W/(K·m), and the aluminum element distribution is more uniform, improving the temperature resistance of the material.
Smart Images

Figure CN118754124B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics, and in particular relates to ordered mesoporous aluminum silicon carbide and a preparation method thereof. Background Art
[0002] Silicon carbide (SiC) is widely used in aerospace, military and defense fields. In order to further improve the temperature resistance of silicon carbide, adding heterogeneous elements to it has attracted widespread attention. Among many elements, the introduction of aluminum makes silicon carbide have the best temperature resistance. However, the flight of aerospace vehicles and the hot end components of aircraft engines will be subjected to severe load impacts and high temperatures, so there are higher requirements for the performance of aluminum silicon carbide materials.
[0003] Mixing with aluminum alloy in any proportion has more advantages in preparing high-performance aluminum-based silicon carbide composite materials. The Chinese invention patent document with publication number CN117447208A discloses a one-step synthesis method of porous silicon carbide / aluminum composite materials, using organic precursors as template materials, silicon carbide powder and alumina as raw materials, and pressing and calcining to obtain ordered mesoporous silicon carbide / aluminum composite materials. Although fully mixed, in the argon calcination atmosphere, the organic template will have carbon residues in the material, causing pore blockage, reducing thermal conductivity and affecting the purity of the material.
[0004] The Chinese invention patent document with publication number CN107540378A discloses a method for preparing a silicon carbide / aluminum composite material, in which a silicon carbide raw material and aluminum powder are mixed and reacted in a vacuum to prepare an aluminum-based silicon carbide composite material. Not only are the reaction conditions harsh, but the product uniformity is poor due to the aluminum infiltration method, and the thermal conductivity is lower than 176W / (K·m). Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing ordered mesoporous aluminum silicon carbide with uniform aluminum distribution. The prepared aluminum silicon carbide product has regular and orderly pores, a large specific surface area and good thermal conductivity.
[0006] To solve the above problems, the present invention adopts the following technical solutions:
[0007] On the one hand, the present invention provides an ordered mesoporous aluminum silicon carbide, wherein the ordered mesoporous aluminum silicon carbide is a three-dimensional cubic ordered mesoporous structure or a two-dimensional hexagonal ordered mesoporous structure; the mass ratio of the elements aluminum, silicon and carbon in the ordered mesoporous aluminum silicon carbide material is 1:11.5:4.9-1:5.4:2.3; the ordered mesoporous aluminum silicon carbide with a three-dimensional cubic ordered mesoporous structure has a specific surface area of 576-624 cm 2 / g, pore size is 4.9-5.8nm; the ordered mesoporous aluminum silicon carbide of the two-dimensional hexagonal ordered mesoporous structure has a specific surface area of 432-468 cm 2 / g, and the pore diameter is 6.1-6.9nm.
[0008] Preferably, the thermal conductivity of the ordered mesoporous aluminum silicon carbide with the three-dimensional cubic ordered mesoporous structure is 201-208 W / (K·m); the thermal conductivity of the ordered mesoporous aluminum silicon carbide with the two-dimensional hexagonal ordered mesoporous structure is 190-196 W / (K·m).
[0009] In another aspect, the present invention provides a method for preparing ordered mesoporous aluminum silicon carbide, comprising the following steps:
[0010] (1) adding organic aluminum and polycarbosilane to xylene for hydrothermal reaction to generate a xylene suspension of aluminum silicon carbide precursor PACS, and performing solid-liquid separation and drying to obtain aluminum silicon carbide precursor PACS;
[0011] (2) Dissolve the precursor PACS in n-hexane, stir and dissolve, then add ordered mesoporous silica, and continue stirring until the n-hexane is completely volatilized, so that the precursor PACS fills the pores of the ordered mesoporous silica to obtain solid PACS@SiO2;
[0012] (3) calcining the solid PACS@SiO2 to obtain AlSiC@SiO2;
[0013] (4) Add AlSiC@SiO2 to a sodium hydroxide solution, stir to remove the ordered mesoporous silica, separate the solid and liquid, and dry to obtain ordered mesoporous aluminum silicon carbide.
[0014] Preferably, in step (1), the organoaluminum is any one of 8-hydroxyquinoline aluminum, aluminum acetylacetonate or aluminum stearate; the molar ratio of the organoaluminum to polycarbosilane is 1:5-10; the mass volume ratio of polycarbosilane to xylene is 1 g:5-10 mL, the hydrothermal reaction temperature is 130-160° C., and the reaction time is 12-36 h.
[0015] Preferably, in step (2), the mass volume ratio of the precursor PACS, ordered mesoporous silica and n-hexane is 1 g: 0.5-2 g: 5-10 mL; and the ordered mesoporous silica is SBA-15 or KIT-6.
[0016] Preferably, in step (3), the calcination process is: firstly heating to 300-400°C, maintaining the temperature for 1-2 hours, then heating to 500-700°C, maintaining the temperature for 0.5-1 hour, then heating to 1200-1400°C, maintaining the temperature for 1-3 hours.
[0017] Preferably, in step (4), the molar ratio of AlSiC@SiO2 to sodium hydroxide is 1:2-4; and the stirring time is 8-24 hours.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The prior art uses organic templates, which not only leave carbon residues inside the pores, but also easily collapse during the calcination process, resulting in pore blockage in the product, which causes the specific surface area of the product to decrease, and ultimately reduces the thermal conductivity. The technical solution of the present invention uses ordered mesoporous silica as a hard template, and utilizes its ordered mesoporous structure to fully fill the aluminum silicon carbide precursor into the pores of the silica, and then uses sodium hydroxide to dissolve the silica, and then reversely replicates to obtain aluminum silicon carbide with an ordered mesoporous structure. The ordered structure of the ordered mesoporous aluminum silicon carbide not only has regular pores, but also has a good thermal conductivity. , large specific surface area, good connectivity and strong thermal conductivity; the ordered mesoporous silica is SBA-15 or KIT-6, among which KIT-6 is preferred, which has a three-dimensional cubic ordered mesoporous structure and better connectivity; the mass ratio of aluminum silicon carbide to ordered mesoporous silica is controlled at 1:0.5-2. If it is greater than this ratio, excessive aluminum silicon carbide will block part of the ordered mesoporous channels; if it is less than this ratio, aluminum silicon carbide cannot fill the channel structure of ordered mesoporous silica, resulting in an uneven channel structure. Both of them will cause the problem of poor thermal conductivity.
[0020] (2) In the prior art, silicon carbide powder and aluminum oxide powder are directly mixed and calcined to prepare aluminum-based silicon carbide. The uneven mixing of silicon carbide and aluminum oxide leads to uneven aluminum silicon carbide. The technical solution of the present invention first mixes polycarbosilane, a precursor of silicon carbide, with organic aluminum to form a precursor of aluminum silicon carbide through molecular forces, and then decomposes aluminum silicon carbide through calcination to obtain aluminum silicon carbide with strong uniformity. Compared with the prior art, the aluminum element is more evenly distributed in the aluminum silicon carbide material, further improving the thermal conductivity of the material.
[0021] (3) The prior art uses carbon thermal reduction of silicon carbide to remove the surface silicon dioxide oxide layer, and then mixes and infiltrates with aluminum oxide powder to obtain aluminum silicon carbide material. The preparation method is complicated and the aluminum content in the material is difficult to accurately control. The present invention uses silicon carbide and aluminum precursors to react to form an aluminum silicon carbide precursor. During the preparation process, the organic aluminum content is added according to the demand, and the aluminum silicon carbide precursor is obtained by a hydrothermal reaction with polycarbosilane, which is then heated and decomposed into aluminum silicon carbide. Compared with the prior art, the technical solution of the present invention can more accurately control the aluminum content in the silicon carbide material, and the thermal conductivity of the product is more stable.
[0022] (4) The technical solution of the present invention controls the specific surface area of aluminum silicon carbide to 445-624 cm by the structure of the ordered mesoporous silica in step (2). 2 / g; the pore size is 4.9~6.9nm, and the material can dissipate heat in time through the pores, thus enhancing the thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0024] Figure 1 TEM image of ordered mesoporous aluminum silicon carbide prepared in Example 2;
[0025] Figure 2 TEM image of ordered mesoporous aluminum silicon carbide prepared in Example 5;
[0026] Figure 3 TEM image of ordered mesoporous aluminum silicon carbide prepared in Comparative Example 1. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and the effects of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. Example 1
[0028] Preparation of Ordered Mesoporous Aluminum Silicon Carbide 1
[0029] Aluminum acetylacetonate and polycarbosilane are added to xylene for hydrothermal reaction, the molar ratio of aluminum acetylacetonate to polycarbosilane is 1:5, the mass volume ratio of polycarbosilane to xylene is 1g:5ml, the hydrothermal reaction temperature is 130°C, the reaction time is 12h, and a xylene suspension of PACS, a precursor of aluminum silicon carbide, is generated, and solid-liquid separation and drying are performed to obtain PACS, a precursor of aluminum silicon carbide;
[0030] (2) Dissolve the precursor PACS in n-hexane at a mass volume ratio of 1 g:5 ml. After stirring and dissolving, add SBA-15 at a mass volume ratio of 0.5 g:5 ml. Continue stirring until the n-hexane is completely volatilized, so that the precursor PACS fills the inside of the SBA-15 pores to obtain solid PACS@SiO2.
[0031] (3) Calcinate the solid PACS@SiO2 by first heating it to 300°C and keeping it constant for 1 hour, then heating it to 500°C and keeping it constant for 0.5 hour, then heating it to 1200°C and keeping it constant for 1 hour. AlSiC@SiO2 is obtained.
[0032] (4) Add AlSiC@SiO2 to sodium hydroxide solution, stir to remove ordered mesoporous silica, separate the solid and liquid, and dry to obtain ordered mesoporous aluminum silicon carbide 1. The molar ratio of AlSiC@SiO2 to sodium hydroxide is 1:2. The stirring time is 8 h. Example 2
[0033] Preparation of Ordered Mesoporous Aluminum Silicon Carbide 2
[0034] (1) Aluminum acetylacetonate and polycarbosilane are added to xylene for hydrothermal reaction, the molar ratio of aluminum acetylacetonate to polycarbosilane is 1:8, the mass volume ratio of polycarbosilane to xylene is 1g:8ml, the hydrothermal reaction temperature is 150°C, the reaction time is 24h, and a xylene suspension of aluminum silicon carbide precursor PACS is generated, and the solid-liquid separation and drying are performed to obtain aluminum silicon carbide precursor PACS;
[0035] (2) Dissolve the precursor PACS in n-hexane at a mass volume ratio of 1 g:8 ml. After stirring and dissolving, add KIT-6 at a mass volume ratio of 1 g:8 ml. Continue stirring until the n-hexane is completely volatilized, so that the precursor PACS fills the inside of the KIT-6 pores to obtain solid PACS@SiO2.
[0036] (3) Calcinate the solid PACS@SiO2 by first heating it to 350°C and keeping it at this temperature for 2 hours, then heating it to 600°C and keeping it at this temperature for 1 hour, then heating it to 1400°C and keeping it at this temperature for 2 hours. AlSiC@SiO2 is obtained.
[0037] (4) Add AlSiC@SiO2 to sodium hydroxide solution, stir to remove ordered mesoporous silica, separate the solid and liquid, and dry to obtain ordered mesoporous aluminum silicon carbide 2. The molar ratio of AlSiC@SiO2 to sodium hydroxide is 1:3. The stirring time is 24 hours. Example 3
[0038] Preparation of Ordered Mesoporous Aluminum Silicon Carbide 3
[0039] (1) Adding 8-hydroxyquinoline aluminum and polycarbosilane to xylene for hydrothermal reaction, the molar ratio of 8-hydroxyquinoline aluminum to polycarbosilane is 1:10, the mass volume ratio of polycarbosilane to xylene is 1g:7ml, the hydrothermal reaction temperature is 140°C, the reaction time is 36h, and a xylene suspension of PACS, a precursor of aluminum silicon carbide, is generated. The solid-liquid separation and drying are performed to obtain PACS, a precursor of aluminum silicon carbide;
[0040] (2) Dissolve the precursor PACS in n-hexane at a mass volume ratio of 1 g:5 ml. After stirring and dissolving, add SBA-15 at a mass volume ratio of 1.5 g:5 ml. Continue stirring until the n-hexane is completely volatilized, so that the precursor PACS fills the inside of the SBA-15 pores to obtain solid PACS@SiO2.
[0041] (3) Calcinate the solid PACS@SiO2 by first heating it to 400°C and keeping it constant for 2 hours, then heating it to 500°C and keeping it constant for 0.5 hours, then heating it to 1200°C and keeping it constant for 3 hours. AlSiC@SiO2 is obtained.
[0042] (4) Add AlSiC@SiO2 to sodium hydroxide solution, stir to remove ordered mesoporous silica, separate the solid and liquid, and dry to obtain ordered mesoporous aluminum silicon carbide 3. The molar ratio of AlSiC@SiO2 to sodium hydroxide is 1:4. The stirring time is 16 h. Example 4
[0043] Preparation of Ordered Mesoporous Aluminum Silicon Carbide 4
[0044] (1) Adding 8-hydroxyquinoline aluminum and polycarbosilane to xylene for hydrothermal reaction, the molar ratio of 8-hydroxyquinoline aluminum to polycarbosilane is 1:9, the mass volume ratio of polycarbosilane to xylene is 1g:10ml, the hydrothermal reaction temperature is 160°C, the reaction time is 36h, and a xylene suspension of PACS, a precursor of aluminum silicon carbide, is generated. The solid-liquid separation and drying are performed to obtain PACS, a precursor of aluminum silicon carbide;
[0045] (2) Dissolve the precursor PACS in n-hexane at a mass volume ratio of 1 g:9 ml. After stirring and dissolving, add KIT-6 at a mass volume ratio of 2 g:9 ml. Continue stirring until the n-hexane is completely volatilized, so that the precursor PACS fills the inside of the KIT-6 pores to obtain solid PACS@SiO2.
[0046] (3) Calcinate the solid PACS@SiO2 by first heating it to 400°C and keeping it constant for 1 hour, then heating it to 700°C and keeping it constant for 1 hour, then heating it to 1300°C and keeping it constant for 1 hour. AlSiC@SiO2 is obtained.
[0047] (4) Add AlSiC@SiO2 to sodium hydroxide solution, stir to remove ordered mesoporous silica, separate the solid and liquid, and dry to obtain ordered mesoporous aluminum silicon carbide 4. The molar ratio of AlSiC@SiO2 to sodium hydroxide is 1:2. The stirring time is 8 h. Example 5
[0048] Preparation of ordered mesoporous aluminum silicon carbide 5
[0049] (1) Aluminum stearate and polycarbosilane are added to xylene for hydrothermal reaction, the molar ratio of aluminum stearate to polycarbosilane is 1:8, the mass volume ratio of polycarbosilane to xylene is 1g:8ml, the hydrothermal reaction temperature is 150°C, the reaction time is 24h, and a xylene suspension of aluminum silicon carbide precursor PACS is generated, and the solid-liquid separation and drying are performed to obtain aluminum silicon carbide precursor PACS;
[0050] (2) Dissolve the precursor PACS in n-hexane at a mass volume ratio of 1 g:8 ml. After stirring and dissolving, add SBA-15 at a mass volume ratio of 1 g:8 ml. Continue stirring until the n-hexane is completely volatilized, so that the precursor PACS fills the inside of the SBA-15 pores to obtain solid PACS@SiO2.
[0051] (3) Calcinate the solid PACS@SiO2 by first heating it to 350°C and keeping it constant for 1 hour, then heating it to 600°C and keeping it constant for 0.5 hour, then heating it to 1400°C and keeping it constant for 2 hours. AlSiC@SiO2 is obtained.
[0052] (4) Add AlSiC@SiO2 to sodium hydroxide solution, stir to remove ordered mesoporous silica, separate the solid and liquid, and dry to obtain ordered mesoporous aluminum silicon carbide 5. The molar ratio of AlSiC@SiO2 to sodium hydroxide is 1:3. The stirring time is 20 h. Example 6
[0053] Preparation of Ordered Mesoporous Aluminum Silicon Carbide 6
[0054] (1) Aluminum stearate and polycarbosilane are added to xylene for hydrothermal reaction, the molar ratio of aluminum stearate to polycarbosilane is 1:6, the mass volume ratio of polycarbosilane to xylene is 1g:9ml, the hydrothermal reaction temperature is 140°C, the reaction time is 36h, and a xylene suspension of aluminum silicon carbide precursor PACS is generated, and the solid-liquid separation and drying are performed to obtain aluminum silicon carbide precursor PACS;
[0055] (2) Dissolve the precursor PACS in n-hexane at a mass volume ratio of 1 g:10 ml. After stirring and dissolving, add KIT-6 at a mass volume ratio of 0.5 g:10 ml. Continue stirring until the n-hexane is completely volatilized, so that the precursor PACS fills the inside of the KIT-6 pores to obtain solid PACS@SiO2.
[0056] (3) Calcinate the solid PACS@SiO2 by first heating it to 300°C and keeping it constant for 2 hours, then heating it to 500°C and keeping it constant for 1 hour, then heating it to 1300°C and keeping it constant for 3 hours. AlSiC@SiO2 is obtained.
[0057] (4) Add AlSiC@SiO2 to sodium hydroxide solution, stir to remove ordered mesoporous silica, separate the solid and liquid, and dry to obtain ordered mesoporous aluminum silicon carbide 6. The molar ratio of AlSiC@SiO2 to sodium hydroxide is 1:4. The stirring time is 24 h. Comparative Example 1
[0058] Preparation of ordered mesoporous aluminum silicon carbide 7
[0059] (1) Aluminum acetylacetonate and polycarbosilane are added to xylene for hydrothermal reaction, the molar ratio of aluminum acetylacetonate to polycarbosilane is 1:8, the mass volume ratio of polycarbosilane to xylene is 1g:8ml, the hydrothermal reaction temperature is 150°C, the reaction time is 24h, and a xylene suspension of aluminum silicon carbide precursor PACS is generated, and the solid-liquid separation and drying are performed to obtain aluminum silicon carbide precursor PACS;
[0060] (2) Dissolve the precursor PACS in n-hexane at a mass volume ratio of 1 g:8 ml. After stirring and dissolving, add KIT-6 at a mass volume ratio of 0.3 g:8 ml. Continue stirring until the n-hexane is completely volatilized, so that the precursor PACS fills the inside of the KIT-6 pores to obtain solid PACS@SiO2.
[0061] (3) Calcinate the solid PACS@SiO2 by first heating it to 350°C and keeping it at this temperature for 2 hours, then heating it to 600°C and keeping it at this temperature for 1 hour, then heating it to 1400°C and keeping it at this temperature for 2 hours. AlSiC@SiO2 is obtained.
[0062] (4) Add AlSiC@SiO2 to sodium hydroxide solution, stir to remove ordered mesoporous silica, separate the solid and liquid, and dry to obtain ordered mesoporous aluminum silicon carbide 7. The molar ratio of AlSiC@SiO2 to sodium hydroxide is 1:3. The stirring time is 24 h. Comparative Example 2
[0063] Preparation of ordered mesoporous aluminum silicon carbide 8
[0064] (1) Aluminum acetylacetonate and polycarbosilane are added to xylene for hydrothermal reaction, the molar ratio of aluminum acetylacetonate to polycarbosilane is 1:8, the mass volume ratio of polycarbosilane to xylene is 1g:8ml, the hydrothermal reaction temperature is 150°C, the reaction time is 24h, and a xylene suspension of aluminum silicon carbide precursor PACS is generated, and the solid-liquid separation and drying are performed to obtain aluminum silicon carbide precursor PACS;
[0065] (2) Dissolve the precursor PACS in n-hexane at a mass volume ratio of 1 g:8 ml. After stirring and dissolving, add KIT-6 at a mass volume ratio of 3 g:8 ml. Continue stirring until the n-hexane is completely volatilized, so that the precursor PACS fills the inside of the KIT-6 pores to obtain solid PACS@SiO2.
[0066] (3) Calcinate the solid PACS@SiO2 by first heating it to 350°C and keeping it at this temperature for 2 hours, then heating it to 600°C and keeping it at this temperature for 1 hour, then heating it to 1400°C and keeping it at this temperature for 2 hours. AlSiC@SiO2 is obtained.
[0067] (4) Add AlSiC@SiO2 to sodium hydroxide solution, stir to remove ordered mesoporous silica, separate the solid and liquid, and dry to obtain ordered mesoporous aluminum silicon carbide 2. The molar ratio of AlSiC@SiO2 to sodium hydroxide is 1:3. The stirring time is 24 hours. Comparative Example 3
[0068] Preparation of ordinary aluminum silicon carbide 9
[0069] (1) Adding 8-hydroxyquinoline aluminum and polycarbosilane to xylene for hydrothermal reaction, the molar ratio of 8-hydroxyquinoline aluminum to polycarbosilane is 1:8, the mass volume ratio of polycarbosilane to xylene is 1g:8ml, the hydrothermal reaction temperature is 150°C, the reaction time is 24h, and a xylene suspension of aluminum silicon carbide precursor PACS is generated, and the solid-liquid separation and drying are performed to obtain aluminum silicon carbide precursor PACS;
[0070] (2) Dissolve the precursor PACS in n-hexane at a mass volume ratio of PACS to n-hexane of 1 g:8 ml, stir and dissolve, then add amorphous silica at a mass volume ratio of amorphous silica to n-hexane of 1 g:8 ml, continue stirring until n-hexane is completely volatilized, and obtain solid PACS@SiO2;
[0071] (3) Calcinate the solid PACS@SiO2 by first heating it to 350°C and keeping it at this temperature for 2 hours, then heating it to 600°C and keeping it at this temperature for 1 hour, then heating it to 1400°C and keeping it at this temperature for 2 hours. AlSiC@SiO2 is obtained.
[0072] (4) Add AlSiC@SiO2 to sodium hydroxide solution, stir to remove ordered mesoporous silica, separate the solid and liquid, and dry to obtain ordered mesoporous aluminum silicon carbide 9. The molar ratio of AlSiC@SiO2 to sodium hydroxide is 1:3. The stirring time is 24 h.
[0073] Morphology comparison:
[0074] The JEM-2010 transmission electron microscope (TEM) was used to observe the microstructures of ordered mesoporous aluminum silicon carbide 2, ordered mesoporous aluminum silicon carbide 5 and ordered mesoporous aluminum silicon carbide 7. The samples were fully ground and ultrasonically dispersed in anhydrous ethanol. After standing, the upper layer of solution was dropped on a copper mesh to prepare a sample, which was then dried and tested.
[0075] Figure 1 The microstructure of ordered mesoporous aluminum silicon carbide 2 is shown. Figure 1It can be seen that the ordered mesoporous aluminum silicon carbide is a three-dimensional cubic ordered mesoporous structure; Figure 2 The microstructure of ordered mesoporous aluminum silicon carbide 5 is shown. Figure 2 It can be seen that the ordered mesoporous aluminum silicon carbide is a two-dimensional hexagonal ordered mesoporous structure. The technical solution of the present invention uses ordered mesoporous silica as a hard template and utilizes its ordered mesoporous structure to fully fill the aluminum silicon carbide precursor into the pores of silica. Then, sodium hydroxide is used to dissolve the silica, and aluminum silicon carbide with an ordered mesoporous structure is obtained through reverse replication. The ordered structure of ordered mesoporous aluminum silicon carbide not only has regular pores and a large specific surface area, but also has good connectivity and strong thermal conductivity. Example 2 uses KIT-6 as a hard template. Because KIT-6 has a three-dimensional cubic ordered mesoporous structure, the ordered mesoporous aluminum silicon carbide 2 also has a three-dimensional cubic ordered mesoporous structure ( Figure 1 ); Example 5 uses SBA-15 as a hard template. Since SBA-15 has a two-dimensional hexagonal ordered mesoporous structure, the ordered mesoporous aluminum silicon carbide 5 also has a two-dimensional hexagonal ordered mesoporous structure ( Figure 2 ); Compared with the two, the three-dimensional cubic ordered mesoporous structure has better connectivity, so KIT-6 is the preferred hard template; at the same time, observation of the morphology shows that the structure is arranged regularly and orderly without protruding particles, indicating that the aluminum element is embedded in the silicon carbide lattice and is evenly distributed.
[0076] In the process of preparing ordered mesoporous aluminum silicon carbide, the mass ratio of aluminum silicon carbide to ordered mesoporous silica is controlled at 1:0.5-2. If it is greater than this ratio, the excess aluminum silicon carbide will block part of the ordered mesoporous pores; if it is less than this ratio, aluminum silicon carbide cannot fill the pore structure of the ordered mesoporous silica, resulting in an uneven pore structure. Both of them will cause the problem of poor thermal conductivity. By performing transmission electron microscopy test on the sample of Example 1, the obtained Figure 3 ,from Figure 3 It can be seen that part of its ordered mesoporous structure is covered. This is because the content of aluminum silicon carbide is relatively higher than that of ordered mesoporous silica. During the preparation process, aluminum silicon carbide can not only fill the ordered mesoporous channels, but also easily overflow the channels to cover the channels, reducing the specific surface area of the product, and thus leading to a decrease in thermal conductivity.
[0077] Detection of surface area and pore size
[0078] The specific surface area and pore size of the samples of Examples 1 to 6 and Comparative Examples 1 to 3 were tested using a nitrogen adsorption-desorption instrument, and the thermal conductivity of the samples was tested using a thermal conductivity tester. The results are listed in Table 1.
[0079]
[0080] Examples 1, 3, and 5 are aluminum silicon carbides prepared using SBA-15 as a hard template, and Examples 2, 4, and 6 are aluminum silicon carbides prepared using KIT-6 as a hard template. The results show that the aluminum silicon carbide prepared using KIT-6 as a template has a larger specific surface area than the aluminum silicon carbide prepared using SBA-15 as a template, because KIT-6 is an ordered mesoporous silica with a three-dimensional cubic structure, and its porosity is more developed and the pore connectivity is better. Therefore, the aluminum silicon carbide obtained by its replication also has a three-dimensional cubic structure, a larger specific surface area, better thermal conductivity, and a larger thermal conductivity coefficient. SBA-15 is a two-dimensional hexagonal structure, and the aluminum silicon carbide obtained by its replication is a two-dimensional cubic structure, with a smaller specific surface area than the three-dimensional structure, and poorer pore connectivity than the aluminum silicon carbide with a three-dimensional structure, so its thermal conductivity coefficient is relatively low.
[0081] In the process of preparing aluminum silicon carbide, the ratio of aluminum silicon carbide precursor to ordered mesoporous silica is very important (1g:0.5~2g). Comparative Example 1 is aluminum silicon carbide prepared with a ratio greater than this ratio range (1:0.3), and Comparative Example 2 is aluminum silicon carbide prepared with a ratio less than this ratio range (1:3). The results show that when the ratio of aluminum silicon carbide precursor to ordered mesoporous silica is not within this range, the specific surface area is reduced, the thermal conductivity becomes worse, and the thermal conductivity coefficient is reduced.
[0082] Comparative Example 3 uses amorphous silica as a template to prepare aluminum silicon carbide. Aluminum silicon carbide is obtained by dissolving silica with sodium hydroxide. As a result, its specific surface area is small, and after removing the amorphous silica, the comparative example cannot present a regular pore structure, resulting in its weak ability to dissipate heat, and therefore a low thermal conductivity.
Claims
1. An ordered mesoporous aluminum silicon carbide, characterized in that: The ordered mesoporous aluminum silicon carbide is a three-dimensional cubic ordered mesoporous structure or a two-dimensional hexagonal ordered mesoporous structure; the mass ratio of the elements aluminum, silicon and carbon in the ordered mesoporous aluminum silicon carbide material is 1:11.5:4.9-1:5.4:2.3; the specific surface area of the ordered mesoporous aluminum silicon carbide with the three-dimensional cubic ordered mesoporous structure is 576-624 cm 2 / g, pore size is 4.9-5.8nm; the ordered mesoporous aluminum silicon carbide of the two-dimensional hexagonal ordered mesoporous structure has a specific surface area of 432-468 cm 2 / g, the pore size is 6.1-6.9nm; the thermal conductivity of the ordered mesoporous aluminum silicon carbide with the three-dimensional cubic ordered mesoporous structure is 201-208 W / (K·m); the thermal conductivity of the ordered mesoporous aluminum silicon carbide with the two-dimensional hexagonal ordered mesoporous structure is 190-196 W / (K·m); The method for preparing the ordered mesoporous aluminum silicon carbide comprises the following steps: (1) adding organic aluminum and polycarbosilane to xylene for hydrothermal reaction to generate a xylene suspension of aluminum silicon carbide precursor PACS, and performing solid-liquid separation and drying to obtain aluminum silicon carbide precursor PACS; (2) Dissolve the precursor PACS in n-hexane, stir and dissolve, then add ordered mesoporous silica, and continue stirring until the n-hexane is completely volatilized, so that the precursor PACS fills the pores of the ordered mesoporous silica to obtain solid PACS@SiO2; (3) calcining the solid PACS@SiO2 to obtain AlSiC@SiO2; (4) Add AlSiC@SiO2 to a sodium hydroxide solution, stir to remove the ordered mesoporous silica, separate the solid and liquid, and dry to obtain ordered mesoporous aluminum silicon carbide; In the step (2), the mass volume ratio of the precursor PACS, ordered mesoporous silica, and n-hexane is 1 g: 0.5-2 g: 5-10 mL; the ordered mesoporous silica is SBA-15 or KIT-6; The molar ratio of organic aluminum to polycarbosilane is 1:5-10; the mass volume ratio of polycarbosilane to xylene is 1g:5-10mL.
2. The ordered mesoporous aluminum silicon carbide according to claim 1, characterized in that: In the step (1), the organic aluminum is any one of 8-hydroxyquinoline aluminum, aluminum acetylacetonate, or aluminum stearate; the hydrothermal reaction temperature is 130-160° C., and the reaction time is 12-36 hours.
3. The ordered mesoporous aluminum silicon carbide according to claim 1, characterized in that: In the step (3), the calcination process is: firstly, the temperature is raised to 300-400°C, kept constant at the temperature for 1-2 hours, then the temperature is raised to 500-700°C, kept constant at the temperature for 0.5-1 hour, then the temperature is raised to 1200-1400°C, kept constant at the temperature for 1-3 hours.
4. The ordered mesoporous aluminum silicon carbide according to claim 1, characterized in that: In the step (4), the molar ratio of AlSiC@SiO2 to sodium hydroxide is 1:2-4; and the stirring time is 8-24 hours.
